Remix Culture and English Language Teaching: The Expression of Learner Voice in Digital Multimodal Compositions. Issue 3 (15th September 2015) - Hafner, Christoph A.
Abstract : A number of scholars maintain that the affordances of digital media to easily copy, edit, and share digital content has led to the development of a remix culture in which the amateur creation of cultural artifacts—often remixes, mashups, or parodies based on the creative works of others—has proliferated. At the same time, in TESOL there is increasing interest in engaging students with processes of digital multimodal composition, focusing not only on language proficiency as it is traditionally conceived but also on the strategic use of multimodal resources and collaborative tools to reach a wide authentic audience on the Internet. One issue which such approaches must face is the tendency for some students to draw upon and remix existing creative works in their digital compositions. In particular, the issue is whether this practice of remix promotes or compromises the expression of learner voice. This article considers these questions by examining the multimodal compositions of students in a course in English for science at a Hong Kong university. The analysis generates a theoretical model of remix practices, which can be applied to the teaching and evaluation of multimodal compositions in English language courses.